The degree of employing electronic management skills among public school principals in The West Bank provinces from their Perspectives - Nasser, Alaa Radi; Al-Qasem, Hussam Husni (Journal of Educational and Psychological Sciences, 2023)
The study aimed to identify the degree of using electronic management skills among public school principals in the West Bank from their point of view. And a scale tool was adopted, and it was used in the study scale, and it was confirmed by its validity and reliability. Divide the application of the study scale on a stratified random sample that included (300) male and female managers, from a community consisting of (917) from the six governorates. The results showed that the degree of employing e-management among managers was according to the respondents with average of (3.77 out of 5), with a high estimation. Driving and directing with an average of (3.86), electronic regulation with an average of (3.85), decision-making with an average of (3.71), electronic control with an average of (3.64). The results also showed that there were no differences in the respondents' responses to the degree of application of electronic management due to the variables (gender, practical qualification, and specialization). In light of the results, the researcher recommended enhancing the electronic management skill of public-school principals, and the necessity of holding workshops on an ongoing basis that include principals and teachers of electronic management skills.
Keywords: electronic management; Managers skills; governmental schools; West Bank